Rubber (Hevea brasiliensis) plantations in Orissa: some ecological considerations with reference to soil properties - Gupta C; Edathil T T; George Elsie S; Nageswara Rao K; Punnoose K I
Rubber(Hevea brasiliensis) is comparatively a new crop of commercial importance in the state of Orissa. A total area of approximately 400 ha only has been brought under rubber plantation in the state. The future rubber plantations in the state will be mostly raised in denuded forests and barren lands, thus helping in the state will be mostly raised in denuded forests and barren lands, thus helping in the recuperation of the depredated ecology, besides bringing in socio-economic development.The study was undertaken to quantify the influence of rubber plantation on soil properties. It is observed that the rubber plantations, adopting proper agro-management practices helped in enrichment of organic matter and thus improving the physical properties such as bulk density and moisture retention. An iincrease in organic matter content in the surface layer was recorded. The moisture retained at the field capacity (-0.033 MPa) is 23;and at permanent wilting point (-1.5 MPa) 13;higher in soils under rubber plantation compared to unplanted condition. The available water storage capacity was higher in rubber soils than the unplanted. In general the organic carbon and available phosphorus status in the surface soil and sub soils was found to be low. However, with regard to available phosphorus the rubber plantation soils were found to be higher in 0-30 cm soil depth as compared to unplanted field. The available potassium content in both the soil layers were in the medium range and varied from 107.6 to 172 kg/ha. Similarly, the available magnesium content was in the higher range and varied from 43.6 to 127.2 kg/ha and the soil pH 5.2 to 5.5. In terms of positive influence on soil properties rubber plantation can be considered a desirable crop for recuperation of depredated ecology in this region.
Keywords: Ecology; Field capacity; Moisture retention; Organic matter; Permanent-wilting point; Soil properties